Tìm x Biết
a) (x-2)^2-(x+1)(x+3)=-7
b) 3x^2 (x-7) + 2 (7-x)=0
c) x^3+(x+3)(x-9)=-27
d) 4x^2-4x +1=(x-2)^2
e) 5x(x-3)-2x+6=0
f) x^2-9-4(x+3)=0
g)x^2-5x=6
K
Khách
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
NT
1
NT
Nguyễn Thị Thương Hoài
Giáo viên
VIP
27 tháng 10 2022
x + 12 = 2
x = 2 - 12
x = -10
x + (-13) = -17 - 15 - x - 8
x - 13 = - 40 - x
x + x = -40 + 13
2x = -27
x = -27/2
BM
0
GA
0
NN
0
NT
1
DN
27 tháng 10 2022
(2x+1)22−4x.(x+3)=9
(2x+1)(2x+1)
−4x.(x+3)=9
2x(2x+1) + 1(2x+1) - 4x.(x+3)=9
4x2 + 2x + 2x + 1 - 4x.(x+3)=9
4x2+4x+1-4x.(x+3)=9
4x2+4x+1-4x2- 12x =9
4x2+4x+1-4x2 - 12x =9
4x2 - 4x2 +4x+1- 12x =9
4x+1- 12x =9
4x-12x+1 =9
-8x+1 =9
-8x=9-1
-8x=8
x=8: -8
x= -1
a.
$(x-2)^2-(x+1)(x+3)=-7$
$\Leftrightarrow (x^2-4x+4)-(x^2+4x+3)=-7$
$\Leftrightarrow x^2-4x+4-x^2-4x-3=-7$
$\Leftrightarrow -8x+1=-7$
$\Leftrightarrow -8x=-8$
$\Leftrightarrow x=1$
b.
$3x^2(x-7)+2(7-x)=0$
$\Leftrightarrow 3x^2(x-7)-2(x-7)=0$
$\Leftrightarrow (x-7)(3x^2-2)=0$
$\Leftrightarrow x-7=0$ hoặc $3x^2-2=0$
$\Leftrightarrow x=7$ hoặc $x=\pm \sqrt{\frac{2}{3}}$
c.
$x^3+(x+3)(x-9)=-27$
$\Leftrightarrow x^3+x^2-6x-27=-27$
$\Leftrightarrow x^3+x^2-6x=0$
$\Leftrightarrow x(x^2+x-6)=0$
$\Leftrightarrow x[x(x-2)+3(x-2)]=0$
$\Leftrightarrow x(x-2)(x+3)=0$
$\Leftrightarrow x=0$ hoặc $x-2=0$ hoặc $x+3=0$
$\Leftrightarrow x=0$ hoặc $x=2$ hoặc $x=-3$
d.
$4x^2-4x+1=(x-2)^2$
$\Leftrightarrow (2x-1)^2=(x-2)^2$
$\Leftrightarrow (2x-1)^2-(x-2)^2=0$
$\Leftrightarrow (2x-1-x+2)(2x-1+x-2)=0$
$\Leftrightarrow (x+1)(3x-3)=0$
$\Leftrightarrow x+1=0$ hoặc $3x-3=0$
$\Leftrightarrow x=-1$ hoặc $x=1$
e.
$5x(x-3)-2x+6=0$
$\Leftrightarrow 5x(x-3)-2(x-3)=0$
$\Leftrightarrow (x-3)(5x-2)=0$
$\Leftrightarrow x-3=0$ hoặc $5x-2=0$
$\Leftrightarrow x=3$ hoặc $x=\frac{2}{5}$
f.
$x^2-9-4(x+3)=0$
$\Leftrightarrow (x-3)(x+3)-4(x+3)=0$
$\Leftrightarrow (x+3)(x-3-4)=0$
$\Leftrightarrow (x+3)(x-7)=0$
$\Leftrightarrow x+3=0$ hoặc $x-7=0$
$\Leftrightarrow x=-3$ hoặc $x=7$
g.
$x^2-5x=6$
$\Leftrightarrow x^2-5x-6=0$
$\Leftrightarrow (x^2-6x)+(x-6)=0$
$\Leftrightarrow x(x-6)+(x-6)=0$
$\Leftrightarrow (x-6)(x+1)=0$
$\Leftrightarrow x-6=0$ hoặc $x+1=0$
$\Leftrightarrow x=6$ hoặc $x=-1$